PENGARUH PEKERJAAN ORANG TUA DAN PRESTASI BELAJAR PRAKARYA DAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA PADA SISWA SMK NEGERI PERTANIAN TERPADU PROVINSI RIAU - Noviani, Shindi; Gimin, Gimin; Sumarno, Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aims to determine the influence of parents job and achievements of craft learning and entrepreneurship on the interest of entrepreneurship in students of SMK Negeri Pertanian Terpadu Provinsi Riau. Population in this study were students of class XII that is as many as 159 students and sample of 114 students with a simple random sampling technique. The data collection of this research is documentation techniques. Data analysis used multiple regression linier. The result of this research is the parents job has no effect on significantly to interest of enterpreneurship which obtained tcount -0,106 < ttable 1,658 and significant value 0,000 < 0,05. Craft enterpreneurial learning achievement significantly effect to interest of enterpreneurship which obtained tcount 2,676 > ttable 1,658 and significant value 0,000 < 0,05. Simultaneously there is a significant influence between parents job and craft enterpreneurial learning achievement where obtained value fcount 3,586 > ftable 3,08 and significant value 0,000 < 0,05.multiple linier regression equation obtained in this research is Y = 26,075 – 0,110x1 + 0,274x2. Seen from the calculating 0f R2 (R square change) obtained value of 0,061. This mean that the contribution of the influence of parents job and craft enterpreneurial learning achievement is 6,1%, over 93,9% influenced by other variable outside this research.Keywords: Parents Job, achievements, craft entrepreneurial learning,interest of entrepreneurship